2021
DOI: 10.1093/schizbullopen/sgab032
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Default Mode Network Connectivity and Antipsychotic Treatment Response in Medication-Naïve First Episode Psychosis Patients

Abstract: Introduction Only a few studies have comprehensively characterized DMN pathology on a structural and functional level, and definite conclusions cannot be drawn due to antipsychotic medication exposure and illness chronicity. The objective of this study was to characterize DMN pathology in medication-naïve first episode psychosis patients (FEP), and determine if DMN structural and functional connectivity (FC) have potential utility as a predictor for subsequent antipsychotic treatment response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Study characteristics are shown in Table 1a , Table 1b , Table 1c . Q1) seventeen studies reported on baseline fMRI-FC and AP-R at follow-up ( Anticevic et al, 2015 , Blazer et al, 2022 , Cadena et al, 2019 , Deng et al, 2022 , Doucet et al, 2020 , Hadley et al, 2014 , Han et al, 2020 , Kraguljac et al, 2016 , Kraguljac et al, 2016 , Li et al, 2020 , Maximo et al, 2021 , Nelson et al, 2022 , Sarpal et al, 2016 , Wang et al, 2019 , Zhang et al, 2019 , Blessing et al, 2020 , Zong et al, 2019 ), Q2) eighteen studies investigated associations between changes in fMRI-FC characteristics before and after treatment related to AP-R ( Anticevic et al, 2015 , Blazer et al, 2022 , Cadena et al, 2019 , Chopra et al, 2021 , Deng et al, 2022 , Duan et al, 2020 , Hadley et al, 2014 , Hadley et al, 2016 , Han et al, 2020 , Kraguljac et al, 2016 , Li et al, 2016 , Li et al, 2020 , Liu et al, 2022 , Sarpal et al, 2015 , Shan et al, 2021 , Wang et al, 2019 , Blessing et al, 2020 , Zong et al, 2019 ), Q3) nine studies investigated the prediction of AP-R based on fMRI-FC ( Cao et al, 2018 , Li et al, 2020 , Li et al, 2020 , Liu et al, 2022 , Sarpal et al, 2016 , Shan et al, 2021 , Zhu et al, 2018 , Blessing et al, 2020 , Nejad et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics are shown in Table 1a , Table 1b , Table 1c . Q1) seventeen studies reported on baseline fMRI-FC and AP-R at follow-up ( Anticevic et al, 2015 , Blazer et al, 2022 , Cadena et al, 2019 , Deng et al, 2022 , Doucet et al, 2020 , Hadley et al, 2014 , Han et al, 2020 , Kraguljac et al, 2016 , Kraguljac et al, 2016 , Li et al, 2020 , Maximo et al, 2021 , Nelson et al, 2022 , Sarpal et al, 2016 , Wang et al, 2019 , Zhang et al, 2019 , Blessing et al, 2020 , Zong et al, 2019 ), Q2) eighteen studies investigated associations between changes in fMRI-FC characteristics before and after treatment related to AP-R ( Anticevic et al, 2015 , Blazer et al, 2022 , Cadena et al, 2019 , Chopra et al, 2021 , Deng et al, 2022 , Duan et al, 2020 , Hadley et al, 2014 , Hadley et al, 2016 , Han et al, 2020 , Kraguljac et al, 2016 , Li et al, 2016 , Li et al, 2020 , Liu et al, 2022 , Sarpal et al, 2015 , Shan et al, 2021 , Wang et al, 2019 , Blessing et al, 2020 , Zong et al, 2019 ), Q3) nine studies investigated the prediction of AP-R based on fMRI-FC ( Cao et al, 2018 , Li et al, 2020 , Li et al, 2020 , Liu et al, 2022 , Sarpal et al, 2016 , Shan et al, 2021 , Zhu et al, 2018 , Blessing et al, 2020 , Nejad et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies reported a difference in baseline FC between AP-R and AP-NR ( Nelson et al, 2022 , Anticevic et al, 2015 , Blessing et al, 2020 , Cadena et al, 2019 , Doucet et al, 2020 , Hadley et al, 2014 , Han et al, 2020 , Kraguljac et al, 2016 , Kraguljac et al, 2016 , Sarpal et al, 2016 , Li et al, 2020 , Wang et al, 2019 , Zhang et al, 2019 , Zong et al, 2019 , Deng et al, 2022 , Blazer et al, 2022 , Maximo et al, 2021 ). Studies included 585 patients of which 408 FE patients and 177 chronic patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al, 2023;Wilson et al, 2020; from the onset of illness, while EP samples (also referred to as early-phase or earlyonset psychosis) typically include individuals within a duration of five years from the onset of illness (Deakin et al, 2018;Holmes et al, 2023;Koshiyama et al, 2018;Vanes et al, 2019;. Some studies define FEP and EP based on the first emergence of psychotic symptoms (Fornito et al, 2013;, while others define FEP and EP based on when treatment began, which may be considered the individual's first contact with a clinician (Breitborde et al, 2009;Flaum et al, 1992;O'Connor et al, 2017;Reid et al, 2019), but may also account for when the individual began taking antipsychotic medication (Dempster et al, 2020;Iwashiro et al, 2016;Jauhar et al, 2018;Lencz et al, 2022;Maximo et al, 2021;Salisbury et al, 2022;Wen et al, 2023). An advantage of basing the definition for FEP or EP on the emergence of symptoms is that one can examine individuals in the earliest stages of illness by accounting for untreated psychosis.…”
Section: Neuropathology Of First-episode and Early Psychosismentioning
confidence: 99%
“…Previous dMRI studies in first-episode psychosis (FEP) have thus far converged on a report of reduced fractional anisotropy (FA) in FEP, 25 but the location and scale of these findings vary across studies. [26][27][28][29][30][31][32][33][34][35][36][37] Other reports have studied changes in the number of streamlines connecting cortical regions, a metric that gives insight into the anatomical makeup of the structural connectome. Results from such analyses have been relatively modest compared to FA.…”
Section: Introductionmentioning
confidence: 99%